ANALISIS LAPORAN KEUANGAN HASIL PENGELOLAAN DANA PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) (Kasus di Gapoktan Srijaya Sari Kecamatan Sukahening Kabupaten Tasikmalaya) - iwan Sugianto (JURISMA : Jurnal Riset Bisnis & Manajemen, 2016)
Rural Agribusiness Development Program (PUAP) implemented by the farmers (owners or tenants), farm laborers and poor farm households through coordination diperdesaan Gapoktan as an institution that is owned and managed by farmers. Gapoktan important role as a social institution peasant economy to be important in increasing production and the welfare of farmers. Given the role of the performance evaluation results gapoktan need to be input in developing Gapoktan development model so that it can better contribute in accelerating the improvement of the welfare of farmers, the growth of the agricultural sector and economic development of rural areas.Â The purpose of this research was to determine results financial statement analysis Gapoktan Srijaya Sari subdistrict Sukahening using Financial Ratios through Ratios Profitability who aim to measure the ability Gapoktan Srijaya Sari to generate profit, by using an approach on the calculation of Return On assest (ROA) and Return On Equity (ROE).Results in mind that the results of Financial Statement Analysis Rural Agribusiness Development (PUAP) which has been managed by Gapoktan Srijaya Sari subdistrict Sukahening has shown a number of very good because it has to generate profits for the group union. This is evident from the results with regard Profitability Ratios ROA calculation results (Renturn on Assets) amounted to 16.01% and ROE (ReturnOn Equity) amounted to 25.27%.